2018
DOI: 10.3847/1538-4365/aac724
|View full text |Cite
|
Sign up to set email alerts
|

Subaru High-z Exploration of Low-luminosity Quasars (SHELLQs). IV. Discovery of 41 Quasars and Luminous Galaxies at 5.7 ≤ z ≤ 6.9

Abstract: We report the discovery of 41 new high-z quasars and luminous galaxies that were spectroscopically identified at 5.7 ≤ z ≤ 6.9. This is the fourth in a series of papers from the Subaru High-z Exploration of Low-Luminosity Quasars (SHELLQs) project, based on the deep multi-band imaging data collected by the Hyper Suprime-Cam (HSC) Subaru Strategic Program survey. We selected the photometric candidates using a Bayesian probabilistic algorithm and then carried out follow-up spectroscopy with the Gran Telescopio C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(46 citation statements)
references
References 42 publications
0
45
1
Order By: Relevance
“…More than 200 quasars have been discovered above redshift 5.7 (e.g., Fan et al 2006;Mortlock et al 2009Mortlock et al , 2011Willott et al 2009Willott et al , 2010aVenemans et al 2013Venemans et al , 2015Bañados et al 2014Bañados et al , 2016Bañados et al , 2018Jiang et al 2015Jiang et al , 2016Matsuoka et al 2016Matsuoka et al , 2018Mazzucchelli et al 2017). These high redshift quasars are key to understand the co-evolution between supermassive black holes (SMBHs) and their host galaxies at the end of the reionization epoch.…”
Section: Introductionmentioning
confidence: 99%
“…More than 200 quasars have been discovered above redshift 5.7 (e.g., Fan et al 2006;Mortlock et al 2009Mortlock et al , 2011Willott et al 2009Willott et al , 2010aVenemans et al 2013Venemans et al , 2015Bañados et al 2014Bañados et al , 2016Bañados et al , 2018Jiang et al 2015Jiang et al , 2016Matsuoka et al 2016Matsuoka et al , 2018Mazzucchelli et al 2017). These high redshift quasars are key to understand the co-evolution between supermassive black holes (SMBHs) and their host galaxies at the end of the reionization epoch.…”
Section: Introductionmentioning
confidence: 99%
“…Quasars are powered by supermassive black holes (SMBHs) with ≈ 10 8−10 M⊙ (e.g., De Rosa et al 2014;Wu et al 2015). Owing to wide-area surveys, ≈ 100 quasars are discovered at z > 6 (e.g., Fan et al 2003;Jiang et al 2016;Mazzucchelli et al 2017;Matsuoka et al 2018) and up to z = 7.54 (Bañados et al 2018). How SMBHs have accreted within ≈ 1 Gyr after the Big Bang is one of the most important question in modern astronomy (Valiante et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades, more than 100 z ∼ 6 QSOs have been discovered through wide-field surveys in the optical-near infrared (NIR) wavelengths (e.g., Jiang et al 2009Jiang et al , 2016Willott et al 2010;Venemans et al 2013Venemans et al , 2015Bañados et al 2016;Matsuoka et al 2016Matsuoka et al , 2018. Currently, the most massive BH at z > 6 ever known is J0100+2802 at z = 6.30 (Wu et al 2015), originally identified owing to its red optical color with the dataset of the Sloan Digital Sky Survey (SDSS; York et al 2000), two Micron All Sky Survey (2MASS; Skrutskie et al 2006) and the Wide-field Infrared Survey Explorer (WISE; Wright et al 2010).…”
Section: Introductionmentioning
confidence: 99%